The CGIAR at 31 : An Independent Meta-Evaluation of the Consultative Group on International Agricultural Research, Revised Edition - Operations Evaluation Department (Washington, DC: World Bank, 2013)
The original mission of the CGIAR was a strategic, science-based focus on increasing "the pile of rice on the plates of food-short consumers," as characterized by a former chairman. It was to use the best science in advanced countries to develop technologies for the benefit of food deficit countries and populations. But a rapidly changing external environment has led to an expanded mission and mandate. The mission statement adopted in 1998 is "food security and poverty eradication in developing countries through research, partnerships, capacity building, and policy support, promoting sustainable agricultural development based on the environmentally sound management of natural resources." Several forces continue to influence the CGIAR's mandate. First, the rise of civil society organizations and the empowerment of marginal groups and women have increased donors' attention to social concerns. By restricting their funding to preferred programs and areas, donors are altering the composition of CGIAR activities. Second, water shortages, soil degradation, climate change, and loss of biodiversity have increased the prominence of natural resource management (NRM), policy, and social science research. The new research topics (in which proponents argue the CGIAR has developed a "dynamic comparative advantage") are downstream activities, closer to the farmer, which entail local expertise and solutions, while traditional germplasm improvement research builds on the CGIAR's historical comparative advantage. Third, the growing importance of genetic resource management, the biotechnology revolution, intellectual property rights (IPR), and private sector research call for System-level responses, strategies, and policies.